(untitled) (Research, Society and Development, 2021)
This study aimed to describe the benefits of paternal participation in the pregnancy-puerperal cycle for the consolidation of the father-mother-child triad. This is an integrative literature review, where the survey of the study was carried out between July and August 2021, through the VHL, with the aid of the LILACS, BEDENF and SCIELO Virtual Library databases, using the Health Sciences Descriptors (DeCS): Prenatal; Parent-Child Relationships; and Postpartum Period. After the inclusion and exclusion criteria, 16 studies were selected to compose this study. The results observed in the studies show that the participation of men must occur throughout the pregnancy-puerperal cycle, and must be in tune and in agreement with the partner, and that during this cycle, the monitoring of the man/father can contribute to the minimization of fear , anxieties and anxiety during prenatal care and other feelings during the parturition period, in addition to establishing a greater bond with the mother and the future child. However, it is necessary that health professionals, during the monitoring of pregnant women in prenatal care, encourage the participation of the father figure in monitoring their partner for the consultations, making the bond of the mother-father-child triad possible, which can better strengthen the marital and family relationship.